Internalisasi Maqashid Syariah dalam Tata Kelola Pegawai Negeri Sipil Daerah di Kota Samarinda - Muhammad Nuryadin; Achmad Fauzi Irawan; Birusman Nuryadin (Jurnal Ragam Pengabdian, 2026)
To improve the management of regional civil servants (PNSD) in Samarinda, this study examines the application of the principles of Shariah maqashid. This article highlights five main objectives of Shariah maqashid: maintaining religion (din), protecting the soul (nafs), protecting the mind (aql), protecting descendants/family (nasl/ird), and protecting property (mal). This concept provides a moral foundation for improving the moral character, professionalism, and well-being of civil servants. This study employs a descriptive qualitative research method through a literature review, a series of activities related to the method of collecting library data, reading and writing, and processing of research materials. Internalizing the values of maqashid in shaping the character of ASN is necessary and serves as a practical guide for the government of Samarinda in improving human resources, especially technological ethics. Thus, Shariah maqashid can function as an ethical framework consistent with the ideals of a modern government and at the same time adapted to the needs and culture of Samarinda.